Assessment of the Impact of Political and Economic Factors on Inflation through Multiple Regression Analysis (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study evaluates the impact of political and economic factors on inflation using a multiple regression framework applied to panel data from emerging economies over the period 2000–2024. The results reveal that political stability, money supply growth, fiscal balance, exchange-rate volatility, and trade openness are significant determinants of inflation. Political instability is shown to heighten inflationary expectations, weaken monetary credibility, and amplify external vulnerabilities. Economic factors such as excessive monetary expansion and persistent fiscal deficits also exert upward pressure on prices. The findings underscore that effective inflation control requires not only sound macroeconomic policies but also strong institutions, stable governance, and credible policy frameworks.